How the sea came to be and all the creatures in it - Berne, Jennifer 19XX- (Eerdmans Books for Young Readers, 2023)
"Rhyming text follows the evolution of the ocean, from the fiery time of its birth to the marvelously biodiverse present. Includes notes from the author and illustrator, spotlights on past and present marine life-forms, a timeline of evolutionary eras, a glossary of key terms, and recommended further reading"--
Keywords: Meerestiere; Entstehung; Meer; Ocean / Juvenile literature; Marine animals / Juvenile literature; Marine animals / Evolution / Juvenile literature; Life / Origin / Juvenile literature; Mer / Ouvrages pour la jeunesse; Mer / Origines / Ouvrages pour la jeunesse; Faune marine / Ouvrages pour la jeunesse; Faune marine / Évolution / Ouvrages pour la jeunesse; Vie / Origines / Ouvrages pour la jeunesse; SCIENCE / Life Sciences / Zoology / General; Sachbilderbuch; Kindersachbuch